2010
DOI: 10.1007/s12205-010-0944-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrated lime on dynamic modulus of asphalt-aggregate mixtures in the state of North Carolina

Abstract: A comprehensive experimental study has been conducted primarily to characterize the effect of hydrated lime on a dynamic modulus of Hot Mix Asphalt (HMA). In this paper, five Superpave HMAs typically used in the State of North Carolina were modified with hydrated lime and evaluated with a series of uniaxial compressive complex modulus tests. And a new design method was proposed for lime modified HMAs based on their volumetric optimums. For a 9.5 mm surface mixture, three levels of lime addition methods were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Thus, the horizontal recirculation zone induced by the reversal flow appears at the downstream of the Han River, and the recirculation zone transports back and forth according to the change of tidal constituents. In this tidal reach, [4][5] reported that the oscillatory breakthrough curves were obtained due to the effect of tidal conditions for the continuously spilled pollutants. The storage effect by the tidal current is known as the tidal trapping [6], and several researches [7][8] were published for analysis of the pollutant mixing, in which the retention time of pollutants was increased by the tidal cycle.…”
Section: Introductionmentioning
confidence: 88%
“…Thus, the horizontal recirculation zone induced by the reversal flow appears at the downstream of the Han River, and the recirculation zone transports back and forth according to the change of tidal constituents. In this tidal reach, [4][5] reported that the oscillatory breakthrough curves were obtained due to the effect of tidal conditions for the continuously spilled pollutants. The storage effect by the tidal current is known as the tidal trapping [6], and several researches [7][8] were published for analysis of the pollutant mixing, in which the retention time of pollutants was increased by the tidal cycle.…”
Section: Introductionmentioning
confidence: 88%
“…It was 2005 that the effect of hydrate lime on dynamic modulus and stiffness of the HMA mixture was reported in some studies [7], while some researches were conducted in 2008 and 2009 on the effect of hydrated lime on stripping and moisture damages due to the bitumen-lime filler interaction [8,9]. Meanwhile, some research works were directed in 2010 using hydrated lime in the HMA asphalt to examine the effect it has on the rutting phenomenon in addition to predict the cracking behavior in asphalt [10,11].…”
Section: Objectivementioning
confidence: 99%
“…One other study investigated the effect of optimal content of hydrated lime on aging and workability at high temperatures [17]. In 2011, Lee et al employed modern experimental techniques and new models to study the effect of modified HMA with hydrated lime on rutting and fatigues cracks [11].…”
Section: Objectivementioning
confidence: 99%
“…HL decreases the failure risk of the asphaltaggregate bond mechanically and has a positive effect on this problem even with lack of water in the environment [1,6]. HL increases the tensile strength of the pavements [8,9] by increasing the elasticity modulus of the mixture [10,11]. It especially increases the strength by helping dispersion of the strains caused by traffic loads [12].…”
Section: Introductionmentioning
confidence: 99%